Photolabile chelators for the rapid photorelease of divalent cations. - Kaplan, J H (1988)
The properties of a recently synthesized photolabile chelator for divalent cations are described, the affinity of which for Ca2+ changes by some 5 orders of magnitude on illumination. The compound 1-(2-nitro-4,5-dimethoxyphenyl)-N,N,N',N'-tetrakis[(oxycarbonyl)me thyl]-1,2-ethanediamine (DM-nitrophen) binds Ca2+ (Kd approximately 5.0 x 10(-9) M) and Mg2+ (Kd approximately 2.5 x 10(-6) M) with relatively high affinities. On exposure of the DM-nitrophen-Ca2+ complex to UV light in the 350-nm range, the chelator is cleaved yielding iminodiacetic products with a much lower affinity for Ca (Kd approximately 3 x 10(-3) M) and the free [Ca2+] increases. The quantum yield for Ca2+ release is 0.18. In experiments with chemically skinned skeletal muscle fibers, a fully relaxed fiber equilibrated with DM-nitrophen-Ca2+ complex produced maximal contraction after a single flash from a frequency-doubled ruby laser (347 nm). Half-maximal tension was achieved in approximately 40 ms, some 5 times faster than that obtained after a rapid solution change from a Ca2+-free to a Ca2+-containing solution. In experiments with resealed human erythrocyte ghosts, irradiation of ghosts containing the DM-nitrophen-Ca2+ complex activates a Ca2+-dependent K+ efflux pathway, which is not observed in the absence of illumination. DM-nitrophen is sufficiently stable and photolabile to be used as a caged Ca (or caged Mg) for the rapid photoinitiation of divalent cation-dependent processes over a wide concentration range with a significant increase in temporal resolution over conventional mixing methods.